Manajemen Pengelolaan Asrama Pesantren Terpadu Al-Kahfi Bogor Berbasis Keislaman Dalam Pembentukan Karakter Kemandirian Santri - Azhim Muntholib; Maemunah Sa’diyah (El-Furqania : Jurnal Ushuluddin dan Ilmu-Ilmu Keislaman, 2022)
Pesantren, which is a typical educational institution in Indonesia, has played a major role in the intellectual life of the nation's children. Both intelligent in cognitive, affective and psychomotor aspects. Pesantren has two main focuses in implementing learning programs, namely the learning aspect and the educational aspect. Related to learning, students as subjects in Islamic boarding schools get cognitive knowledge through recitation forums, both classical and sorogan. Meanwhile, in the educational aspect, students gain knowledge and experience related to the affective and psychomotor domains from the boarding education system where students spend the most time interacting with fellow students, ustadz and kiai. Santri when doing activities in the dormitory are required to be independent and responsible. This study intends to describe the management of boarding school management in the formation of the independent character of students. The conclusion obtained by the researcher is that proper planning, organization, implementation, assessment and evaluation as well as the synergy between dormitories, schools and mosques are the keys to the success of pesantren in the pattern of forming the character of the independence of students. Keywords: Boarding Management, Islamic Boarding School, Independence